Fentanyl causes naloxone-resistant vocal cord closure: A platform for testing opioid overdose treatments. (1st October 2021) - Miner, Nicholas B.; Schutzer, William E.; Zarnegarnia, Yalda; Janowsky, Aaron; Torralva, Randy
Highlights: Fentanyl, but not morphine, rapidly induced sustained and lethal vocal cord closure (VCC) in rats. Naloxone prevented, but did not reverse, fentanyl-induced VCC. VCC is a lethal effect of opioid overdose specific to fentanyl that is resistant to naloxone. This model provides a biological platform for testing synthetic opioid overdose treatments. Abstract: Background: High doses of the synthetic opioid fentanyl cause rapid and sustained vocal cord closure (VCC) leading to airway obstruction that prevents overdose victims from breathing. This airway effect is not caused by morphine-derived opiates ( e.g. heroin), is distinct from respiratory depression, resistant to naloxone, and can be lethal. However, VCC has not been previously included in animal models of opioid overdose. Methods: Video laryngoscopy was used to monitor vocal cord movement in anesthetized Sprague-Dawley rats. Rats were administered saline, fentanyl (5, 25, or 50 μg/kg) or morphine (5 mg/kg) in an intravenous (IV) bolus delivered over a 10 s period. The mu opioid receptor (MOR) antagonist naloxone was administered as a pre-treatment (1 mg/kg, IV) 5 min prior to fentanyl (25 μg/kg) or a post-treatment (1 and 2 mg/kg) 1 min after fentanyl (25 μg/kg). Results: Fentanyl (25 and 50 μg/kg) caused sustained and lethal VCC within 10 s. Morphine (5 mg/kg) and fentanyl (5 μg/kg) caused only brief laryngospasm with full recovery. Pre-treatment with naloxone (1 mg/kg) prevented fentanyl-induced VCC, but naloxone (1 and 2 mg/kg) was unable to reverse VCC when administered after fentanyl. Conclusions: These results indicate sustained VCC is a lethal physiological reaction, specific to fentanyl and resistant to naloxone treatment. While pre-treatment with naloxone prevented fentanyl-induced VCC, naloxone was unable to reverse the effect, suggesting a non-opioid receptor-mediated mechanism. These findings demonstrate the necessity of VCC inclusion in animal models of synthetic opioid overdose and the urgent need for more effective treatments for fentanyl-related overdoses.